Developments in the formulation and application of vegetable oil-based metalworking fluids in turning process - Choudhury, I.A.; Lawal, S.A.; Nukman, Y. (Springer Verlag (Germany), 2012)
In the beginning, metalworking fluids consisted of simple oils applied with brushes to lubricate and cool the machine tool. As cutting operations became more severe, metalworking fluid formulation became more complex. There are now several types of metalworking fluids in the market and the most common can be broadly categorized as cutting oils or water-miscible fluids. In this paper, attention is focused on recent research work on formulation and application of vegetable oil-based metalworking fluids in turning process. In addition, the performances of various vegetable oil-based metalworking fluids based on some process parameters such as thrust force, surface roughness, temperature developed at the tool chip interface, and tool wear during turning process using different tool materials were highlighted.